Method for regenerating rare earth roasted ore water leaching liquid filter cloth
By employing a multi-step approach involving high-temperature steam activation, strong acid solution immersion, and surface modification, the clogging problem of rare earth roasted ore leaching solution filter cloth was solved, achieving efficient performance recovery and lifespan extension.
Patent Information
- Application Number
- CN202511500818.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-21
AI Technical Summary
Existing technologies are insufficient to completely remove organic matter, inorganic salts, and other complex compounds from the filter cloth of rare earth roasted ore leaching solution, leading to clogging of the filter cloth mesh, reduced air permeability and filtration efficiency, unsatisfactory cleaning effect, and high cost.
A multi-step method involving high-temperature steam activation, strong acid solution immersion, and surface modification is employed, combined with specific temperatures, times, and solution concentrations, using activators and surface treatment solutions to ensure the recovery of filter cloth performance.
The air permeability of the filter cloth is restored to over 98.5%, and the tensile strength is restored to over 97%, which significantly improves the reuse rate and service life of the filter cloth and reduces production costs.
Smart Images

Figure CN120960877A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of filter cloth cleaning and regeneration, and more particularly to a method for regenerating filter cloth used for rare earth roasting ore water leaching solution. BACKGROUND
[0002] Traditional filter cloth cleaning methods usually include physical cleaning (such as water washing or brushing) and chemical cleaning (such as acid or alkali solution treatment). However, these methods can only remove part of the surface contaminants, but cannot completely restore the original filtering performance of the filter cloth. Especially in the chemical cleaning process, some metal ions (such as aluminum, calcium, magnesium, iron, etc.) on the surface of the filter cloth may react with the cleaning solution to form a complex precipitate, further exacerbating the secondary clogging or damage of the filter cloth, and even reducing its service life. In addition, the existing cleaning and regeneration technology has a series of problems such as unsatisfactory cleaning effect, long regeneration cycle, high energy consumption, and serious resource waste.
[0003] In view of these problems, researchers and engineering and technical personnel in the industry are actively exploring new filter cloth regeneration technology, aiming to completely remove the pollutants on the filter cloth through efficient and environmentally friendly means, and avoid the secondary precipitation and complex formation of metal ions in the cleaning process, so as to restore the filtering performance of the filter cloth, improve its air permeability and strength, and prolong its service life. For example, the comparative patent CN 111167219 A discloses a filter cloth cleaning method, which includes six steps of pre-cleaning, primary cleaning, primary aeration, secondary cleaning, secondary aeration, and filter cloth surface treatment, but it is not suitable for cleaning the filter cloth used for rare earth roasting ore water leaching solution.
[0004] In the process of rare earth roasting ore water leaching solution treatment, filter cloth as a key filter medium is widely used to separate and remove organic matter, inorganic salt and other complex substances in the water leaching solution. These filter cloths are usually made of corrosion-resistant materials and can withstand harsh working conditions, however, as the use time goes on, a large amount of pollutants such as organic matter, inorganic salt and other metal compounds will accumulate on the surface and mesh of the filter cloth. These pollutants will cause the mesh of the filter cloth to be gradually clogged, thereby reducing the air permeability and filtering efficiency of the filter cloth, and affecting the working efficiency and stability of the entire rare earth roasting ore water leaching solution treatment system. In the production site, due to the influence of temperature, ion concentration in the solution and other factors, sometimes the filter cloth is seriously clogged and fails after 1-2 days of use. The main structure of such failed filter cloth is basically intact, the mesh line of the filter cloth is little worn, but all the filter holes are completely clogged, which is difficult to clean with acid, alkali and other cleaning agents, and finally the filter cloth can only be treated as solid waste.
[0005] The existing method does not query the method for cleaning or regeneration of the filter cloth specially used for the rare earth roasting ore water leaching liquid, since the components in the liquid are quite different, although the filter cloth cleaning method used in other fields can remove part of the pollutants to some extent, but there are still the disadvantages of poor cleaning effect, high cost and the like.
[0006] Therefore, how to provide a method for regenerating the filter cloth for the rare earth roasting ore water leaching liquid is a problem to be solved by those skilled in the art. SUMMARY
[0007] Therefore, the present application provides a method for regenerating the filter cloth for the rare earth roasting ore water leaching liquid, effectively overcomes the shortcomings of the conventional cleaning method, restores the original performance of the filter cloth, and greatly reduces the production cost for the enterprise.
[0008] In order to achieve the above-mentioned purpose, the present application provides a method for regenerating the filter cloth for the rare earth roasting ore water leaching liquid, which specifically comprises the following steps: S1, the failed filter cloth with secondary utilization value is screened out, and is subjected to high-temperature steam spraying activation with a configured activator.
[0009] S2, the filter cloth after the treatment in S1 is placed into a strong acid solution for ultrasonic immersion treatment, and then is washed with water until the pH of the surface of the filter cloth is 6-7.
[0010] S3, the filter cloth after the treatment in S2 is subjected to surface treatment, and then is subjected to heat setting treatment, so as to obtain the final regenerated filter cloth.
[0011] The beneficial effects are that through the combination of high-temperature steam spraying activation, acid solution immersion, composite surface modification solution treatment and other steps, the organic matter, inorganic salt and other complex compounds on the filter cloth can be efficiently removed, and at the same time, the reaction of the metal ions with other substances to generate composite precipitates in the cleaning process is avoided, so as to ensure that the mesh of the filter cloth is not blocked again. Secondly, through the strict control of the process parameters such as the specific temperature, time and solution concentration, the performance of the filter cloth is significantly improved, the air permeability of the filter cloth can be restored to more than 98.5% of the original filter cloth, and the breaking strength is restored to more than 97% of the original filter cloth, so that the reutilization rate of the filter cloth is greatly improved.
[0012] The failed filter cloth with secondary utilization value in step S1 refers to the filter cloth whose filtering performance is decreased due to being blocked by complex compounds in the step of solid-liquid separation using the filter cloth after the rare earth concentrate is decomposed and water leached by concentrated sulfuric acid.
[0013] The material of the filter cloth is PP, PE, PPS, PET or PTFE.
[0014] The activator in step S1 is a mixed solution of a strong base and a surfactant, and the molar ratio of the strong base to the surfactant is 1-6:1.
[0015] The mass fraction of all solutes in the mixed solution is 30%-70%.
[0016] The strong base is one or more of NaOH, KOH, NaNH2, KNH2.
[0017] The surfactant is one or more of alkyl phenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyoxyethylene polyoxypropylene ether, betaine, fatty amine polyoxyethylene ether.
[0018] The beneficial effect is that the activator used in the application is different from the traditional solvent and has never been reported in similar literature, and the use of the activator can improve the subsequent acid dissolution effect by more than 70%.
[0019] The temperature of the high-temperature steam blowing activation in step S1 is 120-160 DEG C, and the time is 5-20 min.
[0020] The beneficial effect is that the main role of high-temperature activation is to efficiently activate solid organic pollutants, and the surface and pores of the filter cloth are filled with organic matter and metal salts, which are difficult to dissolve in water, and it is difficult to remove them alone. Acid and alkali can easily damage the filter cloth in ordinary strong alkali solution. High-temperature activation can effectively improve the hydrophilic property of the filter cloth surface, activate organic complex ions, and promote the subsequent acid dissolution effect, which is not only not used in the rare earth field, but also not used in other fields. Method for treating complex solid substances.
[0021] Excessive activation temperature can damage the filter cloth matrix, and after a large amount of research, the high-temperature activation temperature is determined to be 120-160 DEG C, and the activation time is 5-20 min, which can rapidly improve the subsequent acid dissolution effect by more than twice, and will not damage the matrix structure of the filter cloth.
[0022] Step S1 not only applies a new formula, but also applies a new process, and under the operation of the formula and process, a very significant effect of removing pollutants on the surface of the filter cloth is achieved.
[0023] The strong acid solution in step S2 is one or more of HCl, H2SO4, HNO3, HF, CF3SO3H, C5H5SO3H; the acid solution has a substance concentration of 0.5-8 mol / L, and a temperature of 25-95 DEG C.
[0024] The beneficial effect is that after the organic impurities of the solid material on the surface of the filter cloth are removed in step S1, the ion exchange reaction and metathesis reaction can be effectively carried out between the solid material on the surface of the filter cloth and the acid through dissolution and complexation, and good control of the concentration of the acid is an important basis for sufficient reaction, and at the same time, it is also necessary to ensure that the filter cloth is not damaged, so the concentration is the result of a large number of experimental demonstrations. The setting of the acid concentration and temperature range ensures that the filter cloth is not damaged during the cleaning process while thoroughly removing the pollutants.
[0025] The frequency of the ultrasonic soaking treatment in step S2 is 20-40 kHz, and the time is 10-60 min.
[0026] The beneficial effect is that the soaking time determines whether the decomposition of the solid material is sufficient, while also ensuring that the filter cloth material itself is not damaged. Soaking for 10-60 min is the result of a large number of experimental demonstrations. The setting of this time range significantly improves the cleaning effect of the filter cloth.
[0027] The surface treatment in step S3 is soaking the filter cloth in a surface treatment liquid for 1-10 min.
[0028] The surface treatment liquid is 3-aminopropyltrimethoxysilane or 3-chloropropyltrimethoxysilane 1-30 wt%, alkyl benzene sulfonate or alcohol ether sulfate 0.1-15 wt%, polyvinyl alcohol or polyacrylic acid 0.1-15 wt%, polyurethane 0.1-5 wt%, tetrafluoroethylene or polyvinyl fluoride 0.1-5 wt%, and the rest is water and ethanol, with a water:ethanol volume ratio of 5-10:1.
[0029] The beneficial effect is that 3-aminopropyltrimethoxysilane (APTMS) or 3-chloropropyltrimethoxysilane can well increase the hydrophobicity of the filter cloth surface, alkyl benzene sulfonate or alcohol ether sulfate can effectively improve the permeability of the filter cloth, polyurethane, tetrafluoroethylene (PTFE) or polyvinyl fluoride (PVDF) can improve the flexibility of the filter cloth, and water and ethanol are mainly used as solvent media. After the surface treatment agent is prepared according to the given ratio, the performance of the regenerated filter cloth can be significantly improved, further ensuring the air permeability and strength of the filter cloth. The ratio and composition of the surface treatment liquid ensure the overall improvement of the performance of the filter cloth during the regeneration process.
[0030] The heat setting treatment in step S3 is high-pressure steam treatment at 120-200°C for 5-15 min.
[0031] The beneficial effect is that the main role of high-pressure steam setting treatment is to make the modified liquid adsorbed on the surface of the filter cloth more stable and durable, while also ensuring the uniformity and flatness of the filter cloth pores. The setting of this treatment time and temperature range significantly improves the stability and durability of the filter cloth.
[0032] The application also claims the regenerated filter cloth prepared by the above method, wherein the air permeability of the regenerated filter cloth is recovered to more than 98.5% of the original new filter cloth, and the breaking strength is recovered to more than 97% of the original new filter cloth.
[0033] Through the above technical solution, compared with the prior art, the application discloses a method for regenerating a rare earth roasting ore water leaching solution filter cloth, which has the following beneficial effects: (1) In the current filter cloth cleaning technical field, the traditional method cannot avoid the reaction of metal ions with cleaning agents to produce precipitates, resulting in the troublesome problem of secondary blockage. The application initiatively adopts a step-by-step treatment mode of high-temperature activation and acid solution, effectively removes complex pollutants such as organic matter, inorganic salt and metal ions accumulated on the surface and in the mesh of the filter cloth, completely solves the long-term pain point in the industry, and brings unexpected technical breakthroughs.
[0034] (2) In the prior art, there are certain limitations in setting the performance recovery parameters of the filter cloth, and it is difficult for the performance of the filter cloth after cleaning and regeneration to reach a high level. However, after the method of the application is used, the air permeability of the filter cloth is recovered to more than 98.5% of the original filter cloth, and the breaking strength is recovered to more than 97% of the original filter cloth. The filtering efficiency of the regenerated filter cloth almost reaches the original level, far exceeding the performance recovery degree of similar technologies, greatly meeting the high requirements for the performance of the filter cloth in the treatment of rare earth roasting ore water leaching solution, and breaking the conventional selection of the performance recovery parameters of the filter cloth in the prior art.
[0035] (3) The application effectively recovers the filtering performance of the filter cloth and enhances the anti-pollution ability and mechanical strength of the filter cloth through scientific cleaning and surface modification treatment, which is a very rare comprehensive effect in the prior art. The service life of the filter cloth is greatly prolonged, the replacement frequency and related costs are greatly reduced, significant economic and environmental benefits are brought to the industry, and unexpected technical values are shown. BRIEF DESCRIPTION OF DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced. Obviously, the drawings in the following description are only embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of the provided drawings.
[0037] Figure 1 The process flow chart of the application.
[0038] Figure 2 Comparison chart of regenerated filter cloth XRD. DETAILED DESCRIPTION
[0039] With reference to the drawings of the embodiments of the present application, the technical solutions in the embodiments of the present application will be described clearly and completely. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0040] The embodiment of the present application discloses a method for regenerating filter cloth for water leaching solution of rare earth roasting ore.
[0041] Embodiment 1
[0042] (1) The screened filter cloth with secondary utilization value is specifically filter cloth used for solid-liquid separation after rare earth concentrate is decomposed by concentrated sulfuric acid and water leaching, and the filter cloth is blocked by complex compounds, resulting in the decline of the filtering performance; the activator with a molar ratio of NaOH to fatty alcohol polyoxyethylene ether of 1:1 and a total mass fraction of solute of 30% is configured; the screened filter cloth is activated by high-temperature steam blowing of the activator, the temperature is 120°C, and the time is 20 min.
[0043] (2) The filter cloth activated by high-temperature steam blowing is placed in a 0.5 mol / L HCl solution, and is subjected to soaking treatment under the condition of an ultrasonic frequency of 40 kHz, the soaking temperature is 60°C, and the time is 60 min; then the filter cloth is taken out and washed with water until the pH of the surface of the filter cloth is 6.7.
[0044] (3) The filter cloth subjected to high-temperature activation and strong acid soaking treatment is placed in a surface treatment liquid for 10 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 30 wt%, alkyl benzene sulfonate 0.1 wt%, polyvinyl alcohol (PVA) 10 wt%, polyurethane (PU) 3 wt%, tetrafluoroethylene (PTFE) 5 wt%, and the rest is water and ethanol, and the volume ratio of water to ethanol is 10:1.
[0045] Then the filter cloth is taken out and subjected to high-pressure steam setting treatment at 120°C for 5 min to obtain the regenerated filter cloth.
[0046] After detection, the air permeability of the regenerated filter cloth is restored to 98.6% of that of the original filter cloth, and the breaking strength is restored to 97.2% of that of the original new filter cloth.
[0047] Embodiment 2
[0048] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed by concentrated sulfuric acid and water leaching, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with a molar ratio of KOH to polyoxyethylene polyoxypropylene ether of 2:1, and a total mass fraction of solute of 50%; the screened filter cloth is activated by high-temperature steam blowing of the activator, at a temperature of 130°C for 15 minutes.
[0049] (2) The filter cloth activated by high-temperature steam is placed in a mixed solution of H2SO4 and HNO3, the concentration of H2SO4 in the mixed solution is 3 mol / L, and the concentration of HNO3 is 3 mol / L; the soaking treatment is carried out under the condition of an ultrasonic frequency of 30 kHz, at a soaking temperature of 25°C for 30 minutes; then it is taken out and washed with water until the pH of the filter cloth surface is 7.
[0050] (3) The filter cloth treated by high-temperature activation and strong acid soaking is placed in a surface treatment liquid for 5 minutes, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 1 wt%, alkyl benzene sulfonate 15 wt%, polyvinyl alcohol (PVA) 8 wt%, polyurethane (PU) 2 wt%, tetrafluoroethylene (PTFE) 1 wt%, and the rest is water and ethanol, with a volume ratio of water to ethanol of 9:1.
[0051] Then it is taken out and shaped by high-pressure steam at 150°C for 10 minutes to obtain the final regenerated filter cloth.
[0052] After detection, the air permeability of the obtained regenerated filter cloth is restored to 98.7% of the original filter cloth, and the breaking strength is restored to 97.5% of the original new filter cloth.
[0053] Example 3
[0054] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed by concentrated sulfuric acid and water leaching, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with a molar ratio of NaNH2 to betaine of 3:1, and a total mass fraction of solute of 60%; the screened filter cloth is activated by high-temperature steam blowing of the activator, at a temperature of 140°C for 10 minutes.
[0055] (2) The filter cloth activated by high-temperature steam is placed in a mixed solution of HF and C5H5SO3H, the concentration of HF in the mixed solution is 0.5 mol / L, and the concentration of C5H5SO3H is 2 mol / L; the soaking treatment is carried out under the condition of an ultrasonic frequency of 35 kHz, at a soaking temperature of 35°C for 20 minutes; then it is taken out and washed with water until the pH of the filter cloth surface is 6.1.
[0056] (3) The filter cloth treated by high-temperature activation and strong acid soaking is soaked in a surface treatment liquid for 10 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 15 wt%, alkyl benzene sulfonate 10 wt%, polyvinyl alcohol (PVA) 0.1 wt%, polyurethane (PU) 0.1 wt%, tetrafluoroethylene (PTFE) 5 wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 8:1.
[0057] Then, it is taken out and shaped by high-pressure steam at 150°C for 15 min to obtain the final regenerated filter cloth.
[0058] After detection, the air permeability of the obtained regenerated filter cloth is restored to 98.9% of the original filter cloth, and the breaking strength is restored to 97.7% of the original new filter cloth.
[0059] Example 4
[0060] (1) The selected filter cloth with secondary utilization value is the filter cloth used for solid-liquid separation after rare earth concentrate is decomposed by concentrated sulfuric acid and leached by water, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; an activator is prepared by mixing KNH2 and fatty amine polyoxyethylene ether at a molar ratio of 2:1, and the total mass fraction of solute is 70%; the selected filter cloth is activated by high-temperature steam blowing of the activator, the temperature is 150°C, and the time is 5 min.
[0061] (2) The filter cloth treated by high-temperature steam is placed in a 4 mol / L H2SO4 solution and soaked under the condition of ultrasonic frequency 25 kHz, the soaking temperature is 45°C, and the time is 10 min; then, it is taken out and washed with water until the pH of the filter cloth surface is 7.
[0062] (3) The filter cloth treated by high-temperature activation and strong acid soaking is soaked in a surface treatment liquid for 8 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 30 wt%, alkyl benzene sulfonate 15 wt%, polyvinyl alcohol (PVA) 15 wt%, polyurethane (PU) 5 wt%, tetrafluoroethylene (PTFE) 0.1 wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 7:1.
[0063] Then, it is taken out and shaped by high-pressure steam at 200°C for 7 min to obtain the final regenerated filter cloth.
[0064] After detection, the air permeability of the obtained regenerated filter cloth is restored to 99.4% of the original filter cloth, and the breaking strength is restored to 97.7% of the original new filter cloth.
[0065] Example 5
[0066] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed by concentrated sulfuric acid and water leaching, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with KNH2 and betaine at a molar ratio of 3:1, and the total mass fraction of solute is 40%; the filter cloth screened is activated by high-temperature steam blowing with the activator, the temperature is 160°C, and the time is 18 min.
[0067] (2) The filter cloth activated by high-temperature steam is placed in a HNO3 and CF3SO3H solution, the concentration of HNO3 in the mixed solution is 1 mol / L, and the concentration of CF3SO3H is 2 mol / L; the soaking treatment is carried out under the condition of ultrasonic frequency 35 kHz, the soaking temperature is 50°C, and the time is 40 min; then it is taken out and washed with water until the pH of the filter cloth surface is 6.3.
[0068] (3) The filter cloth treated by high-temperature activation and strong acid soaking is placed in a surface treatment liquid for 10 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 10wt%, alkyl benzene sulfonate 10wt%, polyvinyl alcohol (PVA) 5wt%, polyurethane (PU) 3wt%, tetrafluoroethylene (PTFE) 3wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 6:1.
[0069] Then it is taken out and shaped by 200°C high-pressure steam for 9 min to obtain the final regenerated filter cloth.
[0070] After detection, the air permeability of the regenerated filter cloth is restored to 99.3% of the original filter cloth, and the breaking strength is restored to 98.5% of the original new filter cloth.
[0071] Example 6
[0072] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed by concentrated sulfuric acid and water leaching, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with NaOH and alkyl phenol polyoxyethylene ether at a molar ratio of 1:1, and the total mass fraction of solute is 55%; the filter cloth screened is activated by high-temperature steam blowing with the activator, the temperature is 135°C, and the time is 12 min.
[0073] (2) The filter cloth activated by high-temperature steam is placed in a HCl and CF3SO3H mixed solution, the concentration of HCl is 6 mol / L, and the concentration of CF3SO3H is 2 mol / L; the soaking treatment is carried out under the condition of ultrasonic frequency 40 kHz, the soaking temperature is 25°C, and the time is 10 min; then it is taken out and washed with water until the pH of the filter cloth surface is 7.
[0074] (3) The filter cloth treated by high temperature activation and strong acid soaking is put into a surface treatment liquid for 6 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 20 wt%, alkyl benzene sulfonate 7 wt%, polyvinyl alcohol (PVA) 9 wt%, polyurethane (PU) 1 wt%, tetrafluoroethylene (PTFE) 2 wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 5:1.
[0075] Then it is taken out and shaped by high pressure steam at 180℃ for 12 min to obtain the final regenerated filter cloth.
[0076] After detection, the air permeability of the obtained regenerated filter cloth is restored to 98.8% of the original filter cloth, and the breaking strength is restored to 98.2% of the original new filter cloth.
[0077] Comparative Example 1
[0078] (1) The selected filter cloth with secondary utilization value is the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed by concentrated sulfuric acid and leached by water, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; an activator is prepared by mixing NaOH and fatty alcohol polyoxyethylene ether at a molar ratio of 8:1, and the total mass fraction of solute is 30%; the selected filter cloth is activated by high temperature steam blowing of the activator, the temperature is 90℃, and the time is 20 min.
[0079] (2) The filter cloth treated by high temperature steam is put into a 0.4 mol / L HCl solution, and is soaked under the condition of ultrasonic frequency 40 kHz, the soaking temperature is 60℃, and the time is 60 min; then it is taken out and washed with water until the pH of the surface of the filter cloth is 6.7.
[0080] (3) The filter cloth treated by high temperature activation and strong acid soaking is put into a surface treatment liquid for 10 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 30 wt%, alkyl benzene sulfonate 0.1 wt%, polyvinyl alcohol (PVA) 10 wt%, polyurethane (PU) 3 wt%, tetrafluoroethylene (PTFE) 5 wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 4:1.
[0081] Then it is taken out and shaped by high pressure steam at 120℃ for 4 min to obtain the final regenerated filter cloth.
[0082] After detection, the air permeability of the obtained regenerated filter cloth is restored to 85% of the original filter cloth, and the breaking strength is restored to 80% of the original new filter cloth.
[0083] Comparative Example 2
[0084] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed and water leached by concentrated sulfuric acid, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with KOH and polyoxyethylene polyoxypropylene ether at a molar ratio of 12:1, and the total mass fraction of solute is 50%; the filter cloth screened is activated by the activator at a high temperature steam, at a temperature of 130°C for 15 min.
[0085] (2) The filter cloth activated by high temperature steam is placed in a mixed solution of H2SO4 and HNO3, wherein the concentration of H2SO4 is 0.3 mol / L, and the concentration of HNO3 is 0.3 mol / L; the soaking treatment is carried out under the condition of ultrasonic frequency of 30 kHz, at a soaking temperature of 85°C for 30 min; then it is taken out and washed with water until the pH of the filter cloth surface is 7.
[0086] (3) The filter cloth treated by high temperature activation and strong acid soaking is placed in a surface treatment liquid for 5 min, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 1wt%, alkyl benzene sulfonate 15wt%, polyvinyl alcohol (PVA) 8wt%, polyurethane (PU) 2wt%, tetrafluoroethylene (PTFE) 1wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 20:1.
[0087] Then it is taken out and shaped by high pressure steam at 150°C for 20 min to obtain the final regenerated filter cloth.
[0088] After detection, the air permeability of the obtained regenerated filter cloth is restored to 75% of the original filter cloth, and the breaking strength is restored to 70% of the original new filter cloth.
[0089] Comparative Example 3
[0090] (1) The screened failure filter cloth with secondary utilization value, specifically, the filter cloth used for solid-liquid separation after the rare earth concentrate is decomposed and water leached by concentrated sulfuric acid, and the filter cloth is blocked by complex compounds, resulting in a decrease in filtration performance; the activator is configured with NaNH2 and betaine at a molar ratio of 15:1, and the total mass fraction of solute is 60%; the filter cloth screened is activated by the activator at a high temperature steam, at a temperature of 140°C for 10 min.
[0091] (2) The filter cloth activated by high temperature steam is placed in a 5 mol / L HNO3 solution, and the soaking treatment is carried out under the condition of ultrasonic frequency of 60 kHz, at a soaking temperature of 90°C for 20 min; then it is taken out and washed with water until the pH of the filter cloth surface is 6.1.
[0092] (3) The filter cloth treated by high temperature activation and strong acid soaking is put into a surface treatment liquid for 10 minutes, the surface treatment liquid contains 3-aminopropyltrimethoxysilane (APTMS) 0.5wt%, alkyl benzene sulfonate 10wt%, polyvinyl alcohol (PVA) 0.1wt%, polyurethane (PU) 0.1wt%, tetrafluoroethylene (PTFE) 5wt%, and the rest is water and ethanol, and the volume ratio of water and ethanol is 25:1.
[0093] Then it is taken out and shaped by high pressure steam at 150℃ for 30 minutes to obtain the final regenerated filter cloth.
[0094] After testing, the air permeability of the obtained regenerated filter cloth is restored to 80% of the original filter cloth, and the breaking strength is restored to 75% of the original new filter cloth.
[0095] XRD characterization
[0096] The failed filter cloth, the alkali washed filter cloth and part of the regenerated filter cloth in the examples are characterized by XRD, and the results are shown in Figure 2 As can be seen from the figure, the original diffraction peaks of the failed filter cloth have disappeared, which is because a layer of filter residue covers the surface of the filter cloth. After the treatment by the technology, the original diffraction peaks of the filter cloth reappear, which indicates that the filter residue is removed more thoroughly.
[0097] The above description of the disclosed examples enables those skilled in the art to implement or use the present application. Various modifications to these examples will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other examples without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these examples shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for regenerating filter cloth from rare earth roasted ore leaching solution, characterized in that, Specifically, the following steps are included: S1, the filtered, unused filter cloths with secondary utilization value are activated by high-temperature steam blowing with the prepared activator; S2, the filter cloth treated in S1 is immersed in a strong acid solution for ultrasonic soaking, and then rinsed with water until the pH of the filter cloth surface is 6-7. S3 involves surface treatment of the filter cloth after S2, followed by heat setting to obtain the final regenerated filter cloth.
2. The method for regenerating filter cloth from rare earth roasted ore leaching solution according to claim 1, characterized in that, The expired filter cloth with secondary utilization value mentioned in step S1 refers to the filter cloth whose filtration performance has decreased due to being blocked by complex compounds during the solid-liquid separation step after rare earth concentrate is leached by concentrated sulfuric acid decomposition water. The filter cloth is made of PP, PE, PPS, PET, or PTFE.
3. The method for regenerating filter cloth from rare earth roasted ore leaching solution according to claim 1, characterized in that, The activator mentioned in step S1 is a mixed solution of a strong base and a surfactant, wherein the molar ratio of the strong base to the surfactant is 1-6:1; The mass fraction of all solutes in the mixed solution is 30%-70%; The strong base is one or more of NaOH, KOH, NaNH2, and KNH2; The surfactant is one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyoxyethylene polyoxypropylene ether, betaine, and fatty amine polyoxyethylene ether.
4. The method for regenerating filter cloth from rare earth roasted ore leaching solution according to claim 1, characterized in that, The high-temperature steam blowing activation in step S1 is carried out at a temperature of 120-160℃ for 5-20 minutes.
5. The method for regenerating filter cloth from rare earth roasted ore leaching solution according to claim 1, characterized in that, The strong acid solution mentioned in step S2 is one or more of HCl, H2SO4, HNO3, HF, CF3SO3H, and C5H5SO3H; the concentration of the acid solution is 0.5-8 mol / L, and the temperature is 25-95℃.
6. The method for regenerating filter cloth from rare earth roasted ore leaching solution according to claim 1, characterized in that, The ultrasonic immersion treatment in step S2 has a frequency of 20kHz-40kHz and a duration of 10-60min.
7. The method for regenerating a filter cloth from a rare earth roasted ore leaching solution according to claim 1, characterized in that, The surface treatment in step S3 involves immersing the filter cloth in a surface treatment solution for 1-10 minutes.
8. The method for regenerating a filter cloth from a rare earth roasted ore leaching solution according to claim 7, characterized in that, The surface treatment solution consists of 1-30 wt% 3-aminopropyltrimethoxysilane or 3-chloropropyltrimethoxysilane, 0.1-15 wt% alkylbenzene sulfonate or alcohol ether sulfate, 0.1-15 wt% polyvinyl alcohol or polyacrylic acid, 0.1-5 wt% polyurethane, 0.1-5 wt% tetrafluoroethylene or polyvinyl fluoride, with the remainder being water and ethanol, in a water:ethanol volume ratio of 5-10:
1.
9. The method for regenerating a filter cloth from a rare earth roasted ore leaching solution according to claim 1, characterized in that, The heat setting treatment in step S3 is a high-pressure steam treatment at 120-200℃ for 5-15 minutes.
10. A regenerated filter cloth prepared by the method according to any one of claims 1-9, characterized in that, The regenerated filter cloth has an air permeability that is restored to more than 98.5% of that of the original new filter cloth, and a tensile strength that is restored to more than 97% of that of the original new filter cloth.
Citation Information
Patent Citations
Method for cleaning multifilament filter cloth for copper concentrate pressure filtration
CN103585821A
Filter cloth cleaning method
CN111167219A
Cleaning process of cartridge filter element
CN111318086A
Filter cloth for treating rare earth smelting oily wastewater and preparation method thereof
CN113521881A
Method for prolonging service time of sulfuric acid rare earth leaching slurry filtering cloth and application
CN118949557A